O processo colonizatório e as relações interétnicas na fazenda Saudades, oeste catarinense: memória, identidade e patrimônio - Frigo, Daiane (2019)
This research aimed to investigate the colonization process and the interethnic relations in the municipalities that made up the old Fazenda Saudades, in the west of Santa Catarina and how this process is inserted in the construction of the regional history, deepening the study on the memories of its inhabitants and the resignification of these experiences under patrimonial optics. The methodology used included the study of different sources and documents that deal with the settlement and colonization of the West region of Santa Catarina, based on the narrative genre of the micro-history and the methodological perspective of the oral history, as a complementary bias of analysis. Thus, interviews were conducted with residents of some of the municipalities that make up the former Fazenda Saudades, in order to consider the point of view of individuals who were part of the historical formation process of the region. The main results of this study indicate the processes of social adaptation by different ethnic groups, since the set of economic, political and social factors resulting from the colonization led to the emergence of assimilation processes, but also to the present-day borders. many contexts of the researched region. From the standpoint of cultural heritage, few patrimonial initiatives have been identified and strategies to minimize social injustices, integrating individuals to the margin of the development standard. In this sense, the dialogue between different ethnic groups and the social and cultural frontiers, starting from the fronts of expansion in the former Fazenda Saudades, allow to expose experiences that contribute to new perceptions about the subjects of Santa Catarina West and the formation of the regional space.